Feasible acetic acid fermentations of alcoholic and sugary substrates in combined operation mode. Issue 9 (September 2016) - Gullo, Maria; Zanichelli, Gabriele; Verzelloni, Elena; Lemmetti, Federico; Giudici, Paolo
Graphical abstract: Highlights: Acetic acid fermentations of alcoholic and sugary media. Transition from batch cultivation to a prototype scale. Selected AAB cultures for industrial applications. Static and submerged fermentations via a single acetic acid bacterium strain. Abstract: Starting from small-scale batch cultivations, acetic acid fermentations in static and submerged systems have been performed by a single acetic acid bacterial strain. To provide user-friendly selected starter cultures for industry, the versatility of these cultures in using different oxidation substrates under different conditions was assessed. In all cases, vinegars with the desired acetic acid, residual ethanol and reducing sugar contents were obtained. An appropriate small-scale batch cultivation subjected to strict process control was pivotal for obtaining the desired acetic acid concentrations and an active culture for submerged fermentation. This achievement enabled the generation of selected starter cultures for submerged vinegar production, which reached an acetic acid content of 8.00–9.00% (w/v), as well as prototype-scale vinegar production. The production of vinegars with reducing sugars in the range of 15.00–27.00 (% w/v) was achieved, and cellulose production was avoided. The dominance of the microbial culture in this process was shown via (GTG)5-PCR. These results are valuable for introducing the use of selected acetic acid bacteria cultures in industrial vinegar production.